The Russia-Ukraine Conflict and Its Implications for Regional Security: Assessing the Impact on Pakistan’s Stability and Strategic Interests - Shahbaz, Khdija; Muzaffar, Muhammad (Pakistan Languages and Humanities Review, 2025)
The purpose of this qualitative research is to examine the impact of the conflict between Russia and Ukraine on regional security and Pakistan’s internal stability. The 2014 Russia-Ukraine conflict had far-reaching effects on the geopolitical landscape, threatening the safety and stability of the whole region. The current confrontation between Russia and Ukraine stems from their long history of fighting and their divergent future goals. However, Russia saw Ukraine’s progress towards the EU and NATO as a danger to its own geopolitical interests. Conclusions from the study emphasize the need for a comprehensive assessment of potential threats, including the impact on Pakistan’s bilateral relations with Russia, Ukraine, and other regional actors, as well as the dynamics of Pakistan’s internal security. Pakistan’s commercial, investment, and energy industries face threats as well as opportunities for diversification and strategic partnerships because of the conflict. The study recommends that Pakistan should make concerted diplomatic efforts to encourage communication and de-escalation between the Russian Federation and Ukraine.